Prolong: a double-blind randomised placebo-controlled trial of broccoli sprout extract in women with early onset preeclampsia. A clinical trial protocol - Kirsten R Palmer; Euan M Wallace; Annie G Langston-Cox; Sarah A Marshall (BMJ Open)
Introduction Preeclampsia is a leading cause of maternal and perinatal morbidity and mortality. There is a need for adjuvant, targeted therapies to improve outcomes. Broccoli sprout extract, rich in the antioxidant sulforaphane, reduces oxidative stress and placental secretion of the antiangiogenic factors that contribute to vascular dysfunction in preeclampsia. We propose a phase III trial investigating broccoli sprout extract. We will assess broccoli sprout extract in women with early onset (<34 weeks) preeclampsia, investigating (1) the interval between enrolment and delivery (days), (2) biomarkers of placental and endothelial function and (3) maternal and fetal outcomes.Methods A double-blind, placebo-controlled randomised trial will be conducted at Monash Health, Melbourne, Australia. One hundred and eighty women (45 each arm of each stratum) with early onset preeclampsia (defined as per Society for Obstetric Medicine of Australia and New Zealand guidelines) will be recruited. Consenting women will be randomised to receive an oral dose of either broccoli sprout extract (24 mg of activated sulforaphane) or identical placebo, twice daily until delivery. Maternal blood will be collected antenatally for measurement of biomarkers of preeclampsia, including soluble fms-like tyrosine kinase 1 (sFlt-1), placental growth factor (PlGF), soluble endoglin (sEng) and activin A, as well as circulating sulforaphane metabolites. Maternal and perinatal outcomes will be monitored throughout. All clinical care decisions, including the timing of delivery, will be made by the treating team, blinded to treatment allocation. Participation in this trial will not affect routine care. At delivery, maternal and cord blood and placentae will be collected to measure sulforaphane metabolites and sFlt-1, PlGF, sEng and activin A.Ethics and dissemination Approval to conduct the trial has been granted by Monash Health Human Research and Ethics Committee (RES-18-0000-109A). Deidentified data will be published in peer-reviewed journals and presented at learnt society conferences, both nationally and internationally. This study has not yet commenced and is pre-results.Trial registration numberACTRN12618000216213